Unexpected Repigmentation of Vitiligo Universalis Following Hemodialysis Initiation: A Rare Case Report and Literature Overview - Alnoshan AA; Alrashdi FH; AlDahash RA; Nagshabandi KN; Alotaibi S (Dove Medical Press, 2024)
Abdulaziz A Alnoshan,1 Fahad Hamoud Alrashdi,1 Rawan Abdulaziz AlDahash,2 Khalid Nabil Nagshabandi,3 Salman Alotaibi1 1Department of Dermatology, Security Forces Hospital, Riyadh, Saudi Arabia; 2Department of Dermatology, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 3Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Khalid Nabil Nagshabandi, Department of Dermatology, College of Medicine, King Saud University, PJ7C+89Q, Riyadh, 12372, Saudi Arabia, Tel +966-582940888, Email khaloed23@gmail.comAbstract: Vitiligo is a chronic skin depigmentation disorder affecting 0.2- 1.8% of the global population, with a significant prevalence in Saudi Arabia. Although not life-threatening, it severely impacts the quality of life and psychological well-being of patients. We report a rare instance of hemodialysis-induced skin repigmentation involving a 25-year-old woman with vitiligo universalis.Keywords: hemodialysis, repigmentation, vitiligo, vitiligo universalis